An ultrasensitive electrochemical aptasensor based on Pd@PCN-222 as a signal probe coupled with exonuclease III-assisted cycling amplification for the detection of ochratoxin A. (September 2022) - Wu, Chengyuan; Wu, Xiangchuan; Hou, Fan; Wu, Lina; Liu, Guangxia
Abstract: An ultrasensitive electrochemical aptasensor was established based on metalloporphyrin metal organic frameworks (Pd@PCN-222) with peroxidase-like activity and exonuclease III-assisted recycling magnification for the detection of ochratoxin A (OTA). Pd@PCN-222 showed well peroxidase-like activities due to Fe-tetrakis (4-carboxyphenyl) porphyrin (Fe-TCPP) as a heme-like ligand and in situ supported with palladium nanoparticle, which could be used for the label of ssDNA instead of nature enzyme. The designed exonuclease III-assisted recycling magnification further improve the sensitivity for the detection. Based on this, the proposed aptasensor showed a well linear relationship within the scope of 1 × 10 −5 ng mL −1 to 10 ng mL −1 and a low detection limit of 6.79 fg mL −1 . Additionally, the application in the real spiked oil samples confirmed the dependability and veracity of the aptasensor. Hence, the designed aptasensor has comprehensive application prospects for the detection of OTA in food. Highlights: The Pd@PCN-222 was used to label ssDNA instead of nature enzyme. The Pd@PCN-222 and exonuclease III recycle amplified the electrochemical signal. The aptasensor realized trace detection of OTA with a lower LOD of 6.79 fg mL −1 .